Diaphragmatic crus indentation to the renal artery: Is it a new etiology for renovascular hypertension in adults? - Dilek Akkurt Acar; Atilla Hikmet Çilengir; Mehtap Balaban; Eren Çamur; Betül Akdal Dölek; Nilgün Işıksalan Özbülbül (Northwestern Medical Journal)
Aim: To investigate the relationship between hypertension and the indentation and compression of the diaphragmatic crus in the renal artery.